Gunshot suicides in England--a multicentre study based on coroners' records. - Sutton, L; Hawton, K; Simkin, S; Turnbull, P; Kapur, N; Bennewith, O; Gunnell, D (2005)
BACKGROUND: Gunshot suicides account for 2.5% of suicides in England and Wales. This amounts to more than 100 deaths per year. Information about such deaths may assist in the development of suicide prevention strategies. METHOD: We have examined coroners' inquest records for all gunshot suicides between 1st January 2000 and 31st December 2001 in 24 coroners' jurisdictions in England. RESULTS: Fifty-eight gunshot suicides were identified, including one homicide-suicide. Ninety-three per cent of cases were male. Sport or occupational usage was the main reason for owning the gun. Ten per cent were farmers or farm-workers. In 20% of cases the gun did not belong to the individual who used it for suicide. This was more likely in younger suicides. Seven (12.1%) individuals used illegally owned handguns. Large amounts of alcohol had been consumed before the act in nine cases. Nearly three-quarters (72.9%) of individuals with diagnostic information had a probable diagnosis of depression. However, only 22.4% had ever had contact with psychiatric services. Two shotgun certificate holders were under the care of psychiatric services at the time of their death and two others had a history of previous self-harm. CONCLUSIONS: Strategies to reduce the number of gunshot suicides need to focus on limiting access to guns. These include restricting access to guns by non-certificate holders and those who may be at increased risk of suicide, and holding regular gun amnesties.